Rapid characterization of crude oil by NMR relaxation using new user-friendly software. (15th July 2022) - Canan, Talha Furkan; Ok, Salim; Al-Bazzaz, Waleed; Ponnuswamy, Shunmugavel; Fernandes, Michael; Al-Shamali, Mustafa; Qubian, Ali; Sagidullin, Alexander
Graphical abstract: Highlights: The NMR relaxation was correlated to physicochemical properties of crude oils. Facile workflow is shown with specially developed user-friendly software used to determine physical properties of crude oils. Characterization/identification duration of crude oils becomes shorter compared to standard ASTM methods. Abstract: This study demonstrates the feasibility of using low-field nuclear magnetic resonance (LF-NMR) relaxometry for the identification and characterization of crude oils as an alternative and robust technique. In general, the NMR relaxometry is based on monitoring nuclear spin dynamics (molecular dynamics) and analyzing its dependencies on the physicochemical properties of samples. The approach reported in this study comprises the initial analysis of crude oils by several standard American Society for Testing and Materials (ASTM) methods followed by a series of routine LF-NMR measurements. The LF-NMR based method showed the following practical advantages: It is non-destructive, requires minimum sample preparation without hazardous solvents, which helps keeping analysis costs reasonably low. The NMR analysis itself is fast and takes a few seconds for a crude oil sample. The whole method workflow is simple and easy to perform in specially developed user-friendly software that was "trained" to determine physical properties including kinematic viscosity, density, o API gravity, sulfur content, total acid number, refractive index, specific gravity, asphaltene content, microcarbon residue of crude oils using empirical correlations between the oil properties and experimental NMR relaxation values.